2017
DOI: 10.1038/ijir.2017.25
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of erectile dysfunction and associated psychological distress in Chinese men with type 2 diabetes mellitus

Abstract: To estimate the prevalence of erectile dysfunction (ED) and the level of psychological distress and to assess the inter-associations of them among type 2 diabetic men, a cross-sectional observational study of 335 men with type 2 diabetes and 284 men without diabetes from a hospital in Hefei city, Anhui province, China, was conducted. The erectile function was assessed using the five-item version of the International Index of Erectile Function scale (IIEF-5). The evaluation of psychological distress was complet… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(14 citation statements)
references
References 35 publications
0
14
0
Order By: Relevance
“…The Massachusetts Male Ageing Study (MMAS) demonstrated a direct correlation between indexes of anger, depression and ED within middle‐aged to senior groups (40–70 years) (Feldman et al, 1994). Anxiety and depression evaluated by the SCL‐90‐R subscales were correlated with IIEF‐5 scores in type 2 diabetes mellitus patients (Chen et al, 2017). Furthermore, among patients with ED alone or ED combined with premature ejaculation, patients diagnosed with worse ED (measured by the IIEF) had worse psychological conditions (Mourikis et al, 2015).…”
Section: Introductionmentioning
confidence: 99%
“…The Massachusetts Male Ageing Study (MMAS) demonstrated a direct correlation between indexes of anger, depression and ED within middle‐aged to senior groups (40–70 years) (Feldman et al, 1994). Anxiety and depression evaluated by the SCL‐90‐R subscales were correlated with IIEF‐5 scores in type 2 diabetes mellitus patients (Chen et al, 2017). Furthermore, among patients with ED alone or ED combined with premature ejaculation, patients diagnosed with worse ED (measured by the IIEF) had worse psychological conditions (Mourikis et al, 2015).…”
Section: Introductionmentioning
confidence: 99%
“…There are many theories on hypogonadism and erectile dysfunction in diabetes, with causes ranging from vasculopathy to neuropathy and endocrinopathy [ 4 ]. Some studies have even claimed psychogenic causes to be one of the most challenging treatment dilemmas for patients with diabetic erectile dysfunction [ 5 ]. However, it is unknown at present whether diabetes brings about any changes in the personal effects that result in erectile dysfunction or there are any other underlying factors that cause changes in the psychology of the patients [ 6 ].…”
Section: Discussionmentioning
confidence: 99%
“…The study was conducted following the principles of good clinical practice, as laid down in the Declaration of Helsinki, after approval of its synopsis by the ethical review board of Allama Iqbal Medical College, Lahore. A sample size of 160 cases was calculated using a 95% confidence level and a 5% margin of error and taking the expected frequency of hypogonadism to be 11.8% in patients with Type-II diabetic patients [ 5 ]. Patients aged between 20 and 60 years diagnosed with type-II diabetes mellitus in the past 24 months were recruited in the study using non-probability, consecutive sampling.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Neurogenic ED was diagnosed by identifying a history of spinal cord lesions or pelvic surgery [9]. To evalu-ate the patients' psychological issues, we used a Chinese version of the Symptom Checklist-90 [10][11][12], a multidimensional symptom self-reporting inventory composed of 90 items, each rated on a 5-point scale of distress from 0 (not at all) to 4 (extremely) [13]. The global severity index (GSI) provided a summary score for the number and intensity of psychological distresses, and was determined by adding raw scores from all dimensions divided by the total number of items (90) [14].…”
Section: Subjectsmentioning
confidence: 99%